2019
DOI: 10.29399/npa.23369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Cognition in Neurodegenerative Disorders: An Approach Focusing on BDNF

Abstract: Psychiatric disorders are remarkable health problems that cause a massive social and economic burden, and the issue of their long-term and effective treatment is subjected to discussion. The effect of physical activity and exercise is under investigation in the treatment of the major depressive disorder (MDD) and schizophrenia which are accompanied by cognitive dysfunctions. Scientists focus on the positive effects of exercise on learning, memory and attention parameters while investigating the regulatory role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
0
6
0
1
Order By: Relevance
“…Tais dados, falam a favor dos estudos de Colucci-D'Amato et al (2020) e Gökçe et al (2019). De maneira que, o primeiro relacionou exercícios aeróbios com o aumento dos níveis de BDNF e consequente aumento volumétrico de áreas cerebrais, tais como a região hipocampal.…”
Section: Discussionunclassified
“…Tais dados, falam a favor dos estudos de Colucci-D'Amato et al (2020) e Gökçe et al (2019). De maneira que, o primeiro relacionou exercícios aeróbios com o aumento dos níveis de BDNF e consequente aumento volumétrico de áreas cerebrais, tais como a região hipocampal.…”
Section: Discussionunclassified
“…3 Alterations in many neurobiological and humoral factors have been studied as causal factors underlying the pathophysiology of schizophrenia, including volume and functional deficits of cerebral white and grey matter, attenuated resting state connectivity and task-related activation of certain brain areas; 4,5 several neurotransmitter systems; growth factors, including brain-derived neurotrophic factor (BDNF); and immunerelated mechanisms, especially those related to pro-inflammatory activity. 5,6 Inconsistencies in results confound absolute conclusions, but volumetric and functional deficits of the hippocampus (a brain structure central to learning, memory and cognitive integration) and a decrease in the levels of BDNF (a protein involved in the neuroplasticity Physical exercise and the patient with schizophrenia of the central nervous system) are repeatedly reported. In addition to the neurobiological and humoral factors, polygenetic risk is described as a possible causal factor contributing to both the psychiatric symptoms and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the neurobiological and humoral factors, polygenetic risk is described as a possible causal factor contributing to both the psychiatric symptoms and comorbidities. [6][7][8] Most individuals with schizophrenia have reduced rates of physical activity compared with the general population. Major contributors to this sedentary behaviour include fatigue, partly linked to the effects of antipsychotic medication; somatic comorbidities such as obesity, metabolic and cardiorespiratory health issues; low motivation to exercise, probably related to the negative symptoms of the disorder; lack of confidence, especially anxiety and stress about exercising in public; and a lack of resources or encouragement from others to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have found a positive correlation between this increase in BDNF and cognitive improvement, suggesting a molecular mechanism for the clinical effect. However, some studies have not observed this relationship, so it might be still premature to draw definitive conclusions about this issue ( 54 , 55 ). While aerobic exercise related cognitive benefits have been linked to BDNF upregulation, this putative mechanism needs confirmation ( 56 ).…”
Section: In Patients With Chronic Schizophreniamentioning
confidence: 99%